The Performance of Warm Mix for the Asphalt Concrete - Wearing Course (AC-WC) Using the Asphalt Pen 60/70 and the Sasobit® Additives - Serli Carlina; Bambang Sugeng Subagio; Aine Kusumawati (Institut Teknologi Bandung, 2019)
Hot Mix Asphalt (HMA) is a type of asphalt mixture commonly used as flexible pavement material. However, HMA has weaknesses in terms of high mixing and compaction temperature, resulting in high CO2 and Greenhouse Gas (GHG) emissions which have a negative impact on the environment. Therefore, a type of asphalt with lower mixing and compaction temperatures is needed. One alternative that can be done is to add Sasobit® additives to the asphalt. This study looks for the best contents of Sasobit® additives that can be added into the asphalt so that resulting the lowest mixing and compaction temperatures. The content of Sasobit® additives studied was 1%, 2% and 3% of the asphalt weight, sasobit contents higher than 3% are not recommended because it will cause the asphalt to be more liquid. The results show that the addition of Sasobit® by 3% may reduce the mixing temperature and the compaction temperature of about 70C lower compared to the mixture without Sasobit® additives. Further, this study compares the performance of asphalt mixtures using Sasobit® additives (mixture of Warm Mix Asphalt / WMA) with asphalt mixtures without Sasobit® additives (Asphalt / HMA Hot Mix mixture). The performance studied includes Marshall Stability, UMATTA Resilient Modulus and Fatigue. As a result, the WMA mixture that uses Sasobit® additives of 3% has a stability value of 1160 kg marshall; this value is higher than the Marshall stability obtained for the HMA mixture 1075 kg. However, the UMATTA testing at temperatures of 250C and 450C resulted in the highest resilient modulus in the mixture of WMA (3080 Mpa and 315 Mpa). The fatigue testing shows that WMA mixture is more flexible because it has an elastic modulus value of 4854 MPa and flexural stiffness 4551 MPa in a tensile 500µԐ strain compared to HMA mixture. Hot Mix Asphalt (HMA) merupakan jenis campuran beraspal yang umum digunakan sebagai material perkerasan lentur. Namun, HMA memiliki kelemahan dari sisi temperatur pencampuran dan pemadatan yang tinggi, sehingga menghasilkan gas CO2 dan Gas Rumah Kaca (GRK) yang berdampak buruk terhadap lingkungan. Dengan demikian, dibutuhkan suatu jenis campuran beraspal dengan temperatur pencampuran dan pemadatan yang lebih rendah. Salah satu alternatif yang dapat dilakukan adalah dengan menambahkan zat aditif Sasobit® ke dalam aspal. Penelitian ini mencari kadar zat aditif Sasobit® terbaik yang dapat ditambahkan ke dalam aspal sehingga diperoleh temperatur pencampuran dan pemadatan yang terendah. Kadar zat aditif Sasobit® yang diteliti sebesar 1%, 2% dan 3% terhadap berat aspal, kadar sasobit yang lebih tinggi dari 3% tidak direkomendasikan karena akan mengakibatkan aspal semakin cair. Hasil penelitian menunjukan penambahan kadar zat aditif Sasobit® sebesar 3% dapat menurunkan temperatur pencampuran dan temperatur pemadatan sekitar 70C lebih rendah dibandingkan dengan campuran tanpa zat aditif Sasobit® . Selanjutnya penelitian ini membandingkan kinerja campuran beraspal yang menggunakan zat aditif Sasobit® (campuran Warm Mix Asphalt/WMA) dengan campuran beraspal yang tidak mengggunakan zat aditif Sasobit® (campuran Hot Mix Asphalt/HMA). Kinerja campuran yang diteliti antar lain Stabilitas Marshall, Modulus Resilien UMATTA dan Fatigue. Hasilnya, campuran WMA yang mengggunakan zat aditif Sasobit® sebesar 3% memiliki nilai stabilitas marshall 1160 kg dimana nilai ini lebih tinggi dibandingkan dengan stabilitas marshall yang diperoleh untuk campuran HMA yaitu 1075 kg. Akan tetapi, hasil pengujian UMATTA pada suhu 250C dan 450C menghasilkan nilai modulus resilien tertinggi pada campuran WMA (3080 Mpa dan 315 Mpa). Hasil pengujian kelelahan Campuran WMA lebih lentur dikarenakan memiliki nilai modulus elastisitas 4854 MPa dan flexural stiffness 4551 MPa pada regangan Tarik 500µԐ dibandingkan dengan HMA.